STRUCTURAL-LOGICAL MODEL OF EMERGENCY MANAGEMENT OF THE REGIONAL LEVEL IN THE CONDITIONS OF LIMITED OPERATIONAL POSSIBILITIES OF EMERGENCIES OF EMERGENCIES: Array - Andronov, V.; Burmenko, O.; Soshinskiy, О.; Shevchenko, R. (Municipal economy of cities (Technical science), 2020)
The problem of formation of structural-logical model of emergency management of regional level in the conditions of limited operational possibilities of emergency rescue divisions is considered in the work. The analysis of the current state of the issue of forecasting the effectiveness of emergency rescue units allowed to identify the existing problem in the field of civil defense, namely the lack of adequate mathematical apparatus that would form short-term and long-term forecasts of the dynamics of operational capacity and operational capacity of rescue units based on constantly changing information on the number and quality of regional hazards. The authors believe that this issue can be solved by forming a comprehensive expert-statistical methodology, which in turn is based on the modern idea of ​​the emergency management process in a complex natural-technogenic-social transformations. The study examines the sequence of work on management decisions in terms of limited operational capabilities and formed a range of functional limitations that allows to clearly define the information field of the structural-logical model of emergency management and parameterize direct and feedback within the latter. Structural and logical model of emergency management at the regional level in terms of limited operational capabilities of emergency rescue units, consists of two control circuits: general circuit (sufficient) and additional (limited) circuit, which operates in case of limited operational capabilities of emergency rescue units. It consists of eight blocks, namely: establishing the fact of the existence of limitations of operational capabilities of rescue units, clarification and assessment of the situation in the emergency zone, preparation of management decisions, preparation of proposals for additional forces, application of the latest methods of operational capacity funds, organization of return of additional forces and means to the cities of permanent deployment. The practical significance of the results is the ability to develop, based on the existing structural and logical model of emergency management at the regional level in terms of limited operational capabilities of rescue units, a method of calculating operational capacity and operational capacity of the territorial unit, based on existing and forecast potential levels. , man-made, social and military nature and take into account their interaction.